Eccentric muscle challenge shows osteopontin polymorphism modulation of muscle damage. (13th March 2014) - Barfield, Whitney L.; Uaesoontrachoon, Kitipong; Wu, Chung-Sheih; Lin, Stephen; Chen, Yue; Wang, Paul C.; Kanaan, Yasmine; Bond, Vernon; Hoffman, Eric P.
Abstract : A promoter polymorphism of the osteopontin (OPN) gene (rs28357094) has been associated with multiple inflammatory states, severity of Duchenne muscular dystrophy (DMD) and muscle size in healthy young adults. We sought to define the mechanism of action of the polymorphism, using allele-specific in vitro reporter assays in muscle cells, and a genotype-stratified intervention in healthy controls. In vitro reporter constructs showed the G allele to respond to estrogen treatment, whereas the T allele showed no transcriptional response. Young adult volunteers ( n = 187) were enrolled into a baseline study, and subjects with specific rs28357094 genotypes enrolled into an eccentric muscle challenge intervention [ n = 3 TT; n = 3 GG/GT (dominant inheritance model)]. Female volunteers carrying the G allele showed significantly greater inflammation and increased muscle volume change as determined by magnetic resonance imaging T1- and T2-weighted images after eccentric challenge, as well as greater decrement in biceps muscle force. Our data suggest a model where the G allele enables enhanced activities of upstream enhancer elements due to loss of Sp1 binding at the polymorphic site. This results in significantly greater expression of the pro-inflammatory OPN cytokine during tissue remodeling in response to challenge in G allele carriers, promoting muscle hypertrophy in normal females, but increased damage in DMD patients.